HUBUNGAN ANTARA PERSEPSI TERHADAP PERUBAHAN MENTAL DENGAN AGRESIVITAS VERBAL PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN KEDUNG PANE SEMARANG - Wirohati, Meilina; Sakti, Hastaning; Fauziah, Nailul (Jurnal Psikologi, 2013)
Prisoner defined as a person against the law, sentenced guilty by the court, and must undergo the punishment in jail. Prison has its own purpose as a place for prisoner to change, develop and to recognise themself, never again break the law and become a better man for family, God, and country. Exceeding prison capacity and violence through prisoner can escalate phyisical or non verbal aggresivitiy. This research has purpose to find out the relation between the perception to mental improvement to non verbal agresivity on prisoner in Kedungpane prison Semarang. Population in this research is 329 prisoner and with 220 prisoner as subject. Random sampling technique is used in this research. Participants were ask to complete 28 item of non verbal aggresivity scale (Î±=0.925) and 45 item perception of mental improvement scale (Î±=0.934). Analysis used simple regresion found that rxy= -0.698 with p= 0.001 (p<0.05). Based on this result, concluded that perception of mental improvement has significant negative correlation with non verbal aggresivity. It means non verbal aggresivity could be lower if the prisoner have greater perception of mental improvement and vice versa. Perception of mental improvement has 44.8% effect to nonverbal aggresivity while 55.2% is effected by others.Keywords: Non verbal aggresivity, perception of mental improvement, prisoners